2006
DOI: 10.1385/bmm:4:1:55
|View full text |Cite
|
Sign up to set email alerts
|

Evidence-Based Practices for Safe Patient Handling and Movement

Abstract: Efforts to reduce injuries associated with patient handling are often based on tradition and personal experience rather than scientific evidence. The purpose of this article is to summarize current evidence for interventions designed to reduce caregiver injuries, a significant problem for decades. Despite strong evidence, published over three decades, the most commonly used strategies have strong evidence that demonstrate they are ineffective. There is a growing body of evidence to support newer interventions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
79
0
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 85 publications
(83 citation statements)
references
References 81 publications
2
79
0
2
Order By: Relevance
“…These factors require nurses to do patient-handling activities such as patient lifting, position change, transferring and assisting with movement (Retsas & Pinikahana 1999). Nurses often conduct patient handling by bending their waists and maintaining an uncomfortable posture towards the opposite side of the bed or chair, increasing the risk of back pain (Nelson & Baptiste 2004). Environmental factors in ICUs are also risk factors for back pain.…”
Section: Introductionmentioning
confidence: 99%
“…These factors require nurses to do patient-handling activities such as patient lifting, position change, transferring and assisting with movement (Retsas & Pinikahana 1999). Nurses often conduct patient handling by bending their waists and maintaining an uncomfortable posture towards the opposite side of the bed or chair, increasing the risk of back pain (Nelson & Baptiste 2004). Environmental factors in ICUs are also risk factors for back pain.…”
Section: Introductionmentioning
confidence: 99%
“…1 However, investigation of the risks to which carers in Australia are exposed is limited and it is considered that injury reduction efforts are based on tradition and personal experience rather than scientific evidence. [2][3][4] Morbid obesity has been variously defined, and although it is considered by some to be the point at which a person's body mass index (BMI) exceeds 30, [5][6][7] other authors report it to be the point at which a person's BMI exceeds 40. [8][9][10] Alternatively, some researchers have referred to weight alone to indicate whether or not patients can be defined as morbidly obese and have suggested that the level of morbid obesity has been reached when patients surpass their ideal weight by > 45 kg.…”
Section: Introductionmentioning
confidence: 99%
“…However, a minimal level of SA can be determined by the attentional capacity of an individual [38], and such capacity is affected by many factors such as, for example, workload, time pressure, fatigue, and sleep deprivation [39,40]. In the case of safety training, though training can positively affect worker behaviors, large positive impacts on the incidence of adverse work-related outcomes are not generally expected from training alone [41,42]. The West Virginia Loggers' Safety Initiative (LSI) program evaluated the effectiveness of training over a 4-year period, and found no strong evidence of injury reduction [43], though loggers had increased safety knowledge [44].…”
Section: Safety Concerns and Opinions Of Loggersmentioning
confidence: 99%